(untitled) (Vallis Aurea, 2015)
Interest rates on corporate bank loans in Croatia are rarely discussed in terms of interdependence of the functioning between the financial and the real sectors of national economy.The aim of this paper is to expand knowledge of the level of interest rates on corporate loans in Croatia and their determinants, as well as of the relationship between interest rates and the pace of economic activity.For this purpose, interest rates and interest rate spreads in Croatia are compared to rates and spreads in selected European countries.The paper explores the correlation of interest rates with a variety of potential factors and compares the level of interest rates and spreads with an average growth rate of economic activity.It was found that interest rates on corporate loans in Croatiawere approximately at the same average level of the selected countries within the analyzed period, whereas interest rate spreads were above the average of those countries.However, interest rates on corporate loans and interest rate spreads in the selected countries are significantly above the average of the Eurozone. In between interest rates on corporate loans and a part of the macroeconomic variables as well as the variables of the banking sectors of theanalyzed countries, including Croatia, a strong connectionwithin the correlation matrices is identified. Along with the high interest spreads,the second-lowest rate of economic growth is achieved in Croatia (after Hungary) within the analyzed period.